PERANCANGAN WEBSITE SEBAGAI MEDIA INFORMASI UNTUK ASOSIASI PROFESI HIMPUNAN TEKNIK ILUMINASI INDONESIA - Endah Setyaningsih; Jeanny Pragantha; Amalia Setyowulan; Asrullah Ahmad (PROSIDING SERINA, 2021)
A profession ideally has a professional association, which can be a space for professionals with certain scientific fields and disciplines to carry out activities in accordance with scientific disciplines and ethics. The formation of associations is carried out legally and has clear recognition from the government. Professional associations that aim to become a forum for the professional community should have several alternative information media as an extension of the organization's arm for professionals and the public. Some of the information media that are currently widely used are web pages, Instagram, and YouTube. The Indonesian Illuminating Engineering Society (HTII) is one of the professional associations whose existence has been sufficiently recognized in Indonesia. Established on 7 May 1991 in Jakarta, until now it is still very active in various activities in the field of illumination. The development of HTII is not followed by the presence of information media that can be reached by many people, one of which is the existence of a web site. HTII once had a website page, but there was no continuous improvement, so there was no website page. For this reason, the purpose of implementing this PKM is to create a website page. The existence of a website is a form of communication and information for members and for online registration of new members. This PKM implementation method is in the form of designing a website design, while the program is carried out by other PKM implementers, so that a complete HTII website is formed. The design of the HTII website page uses a design thinking approach in designing the User Interface. Later this website will then be tested heuristically to people who are experts in the field of information and technology. In this activity, a dummy design draft has been produced in the form of an interface page in the form of an offline visual template which is in the program process stage towards a prototype in the form of an interactive page. Suatu profesi idealnya memiliki asosiasi profesi, yang bisa menjadi ruang bagi kalangan professional dengan bidang keilmuan dan disiplin tertentu untuk berkegiatan sesuai dengan disiplin dan etika keilmuan.  Pembentukan asosiasi dilakukan secara legal dan pengakuan yang jelas dari pemerintah. Asosiasi profesi yang bertujuan untuk menjadi wadah bagi masyarakat profesional sebaiknya memiliki beberapa alternatif media informasi sebagai perpanjangan tangan organisasi bagi profesional dan masyarakat umum. Beberapa media informasi yang saat ini banyak dipakai berupa website, instagram, dan youtube. Himpunan Teknik Iluminasi Indonesia (HTII) merupakan salah satu asosiasi profesi yang keberadaannya telah cukup diakui di Indonesia. Berdiri pada 7 mei 1991 di Jakarta, hingga saat ini masih sangat aktif dalam berbagai kegiatan di bidang iluminasi. Perkembangan HTII kurang diikuti dengan kehadiran media informasi yang bisa dijangkau banyak orang, salah satunya adanya website. HTII pernah memiliki website, tapi kurang dilakukan perbaikan berkelanjutan, sehingga menjadi tidak ada websitenya. Untuk itu sebagai tujuan pelaksanaan PKM ini dilakukan pembuatan website. Adanya website adalah sebagai bentuk komunikasi dan informasi bagi para anggota dan untuk pendaftaran anggota baru secara online. Metode pelaksanaan PKM ini berupa merancang desain website, sementara untuk programnya dilakukan oleh pelaksana PKM lainnya, sehingga terbentuk secara lengkap website HTII. Perancangan halaman website HTII menggunakan pendekatan desain thinking dalam merancang User Interface. Nantinya website ini kemudian akan diuji secara heuristic kepada orang-orang yang ahli di bidang informasi dan teknologi. Dalam kegiatan ini telah dihasilkan draft dummy desain yang berupa halaman antarmuka berupa visual template offline yang sedang dalam tahap proses program menuju prototipe berbentuk halaman interaktif.